Genetic analyses of novel compound heterozygous hypodysfibrinogenemia, Tsukuba I: FGG c.1129 + 62_65 del AATA and FGG c.1299 + 4 del A. Issue 148 (December 2016) - Mukai, Saki; Nagata, Kazuhiro; Ikeda, Minami; Arai, Shinpei; Sugano, Mitsutoshi; Honda, Takayuki; Okumura, Nobuo
Abstract: Introduction: We found a novel hypodysfibrinogenemia designated Tsukuba I caused by compound heterozygous nucleotide deletions with FGG c.1129 + 62_65 del AATA and FGG c.1299 + 4 del A on different alleles. The former was deep in intron 8 of FGG (IVS-8 deletion) and the latter in exon 9 of FGG (Ex-9 deletion), which is translated for the γ′-chain, but not the γA-chain. A Western blot analysis of plasma fibrinogen from our patient revealed an aberrant γ-chain that migrated slightly faster than the normal Bβ-chain. Materials and methods: To clarify the complex genetic mechanism underlying Tsukuba I's hypodysfibrinogenemia induced by nucleotide deletions in two regions, we generated two minigenes incorporating each deletion region, transfected them into Chinese Hamster Ovary (CHO) cells, and analyzed RT-PCR products. We also established CHO cells producing the recombinant variant fibrinogen, γ′409ΔA (Ex-9 deletion). Results and conclusions: Minigene I incorporating the IVS-8 deletion showed two products: a normal splicing product and the unspliced product. Minigene II incorporating the Ex-9 deletion only produced the unspliced product. The established γ′409ΔA-CHO cells secreted variant fibrinogen more effectively than normal fibrinogen. Therefore, the aberrant splicing products derived from the IVS-8 deletion cause hypofibrinogenemia most likely due to nonsense-mediated mRNA decay and the partial production of normal γA- and γ′-chains; moreover, the Ex-9 deletion causes hypodysfibrinogenemia due to the absence of normal γA- and γ′-chain production (hypofibrinogenemia) and augmented aberrant γ′-chain production (dysfibrinogenemia). Highlights: We identified a novel compound heterozygous hypodysfibrinogenemia patient. He had two deletions one in intron 8 and one in exon 9 of FGG . Both existed in different alleles. The deletion in intron 8 results in hypofibrinogenemia. The deletion in exon 9 leads to hypodysfibrinogenemia.